STAT Family Protein Expression and Phosphorylation State during moDC Development Is Altered by Platinum-Based Chemotherapeutics - Nienke de Haas; Coco de Koning; Stefania di Blasio; Georgina Flórez-Grau; I. Jolanda M. de Vries; Stanleyson V. Hato (Journal of Immunology Research)
The STAT signaling pathway is important in dendritic cell (DC) development and function. Tumor cells can induce STAT signaling, thereby inhibiting DC maturation and immunostimulatory functions, leading to hampered efficacy of DC-based immunotherapies. Platinum-based chemotherapeutics can inhibit STAT signaling, thereby making them an interesting tool to improve DC development and function. In this study, we provide a comprehensive overview of STAT expression and phosphorylation during DC differentiation and maturation and investigate the effects of platinum drugs on STAT signaling during these processes. Monocytes were differentiated into monocyte-derived DCs (moDCs) with IL-4 and GM-CSF and matured with cytokines or TLR ligands. STAT expression and phosphorylation were analyzed by western blotting, and moDC viability and phenotype were analyzed by flow cytometry. Platinum drugs were added at day 3 of differentiation or at the start of maturation to investigate regulation of the STAT signaling pathway. All STAT proteins were expressed during moDC differentiation and STAT1, STAT5, and STAT6 were phosphorylated. No significant changes occurred in the expression and phosphorylation state of the STAT proteins during differentiation. After maturation with TLR ligands, the expression of STAT1 increased, but other STAT proteins were not affected. Phosphorylation of STAT1 and STAT3 increased during maturation, where TLR ligands induced significantly higher levels of phosphorylation than cytokines. Platinum drugs cisplatin and oxaliplatin significantly inhibited phosphorylation of STAT6 during differentiation and maturation. Treatment did not affect the phenotype or viability of the cells. As STAT6 is an important regulator of DC function, these findings suggest a role for platinum-based chemotherapeutics to enhance DC function via inhibition of STAT signaling, thereby potentially enhancing efficacy of DC-based immunotherapies.